2017
DOI: 10.1111/dom.13157
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids suppress brown adipose tissue function in humans: A double‐blind placebo‐controlled study

Abstract: Prolonged exposure to glucocorticoid suppresses the function of human BAT. The enhancement of energy production and lipogenesis in the face of reduced dissipation of energy as heat suggests that glucocorticoids channel energy towards fat storage after nutrient intake. This is a novel mechanism of glucocorticoid-induced obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 53 publications
1
64
2
1
Order By: Relevance
“…In addition to thermoregulation, BAT plays a role in regulating energy and substrate metabolism after a meal . Energy production is stimulated by nutrient intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to thermoregulation, BAT plays a role in regulating energy and substrate metabolism after a meal . Energy production is stimulated by nutrient intake.…”
Section: Introductionmentioning
confidence: 99%
“…The postprandial increase in energy production comprises heat energy dissipated by BAT and the energy required for processing and storage of nutrients . We have recently reported that glucocorticoids inhibit postprandial BAT thermogenesis, resulting in the channelling of energy which would otherwise be dissipated as heat, towards lipid synthesis . If BAT thermogenesis is stimulated, the converse may occur.…”
Section: Introductionmentioning
confidence: 99%
“…The first study to use IRT to estimate SST was performed in 2011 . Ten studies were then published between 2011 and 2016 , six in 2017 , six in 2018 , and one until April 2019 .…”
Section: Resultsmentioning
confidence: 99%
“…Cold exposure is the main activator of BAT in humans . Most, but not all, of the identified studies ( n = 18; 75%) included cooling protocols, although the duration, temperature, and the way of inducing cooling differed between studies (Figure ). Nine out of these eighteen studies used hands/feet immersion in cold water (temperature 10.8°C ± 8.7°C, duration: 6.1 ± 6.8 minutes) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation